Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174003
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Awareness and Intent in Autonomous Vehicle-Pedestrian Interaction

Abstract: Drivers use nonverbal cues such as vehicle speed, eye gaze, and hand gestures to communicate awareness and intent to pedestrians. Conversely, in autonomous vehicles, drivers can be distracted or absent, leaving pedestrians to infer awareness and intent from the vehicle alone. In this paper, we investigate the usefulness of interfaces (beyond vehicle movement) that explicitly communicate awareness and intent of autonomous vehicles to pedestrians, focusing on crosswalk scenarios. We conducted a preliminary study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(180 citation statements)
references
References 22 publications
7
171
1
1
Order By: Relevance
“…Specifically, various presented information were evaluated to be differently relevant (Ackermann et al, 2019;Merat et al, 2018;Zhang, Vinkhuyzen, & Cefkin, 2018). Information regarding AVs' intention was considered more important than information about whether the vehicle detected the VRU (Mahadevan, Somanath, & Sharlin, 2018). An exploratory study by Merat et al (2018) showed that VRUs rated messages about AVs' starting, stopping and turning maneuvers as significantly more important than information regarding the vehicles' speed.…”
Section: Designing Interactions In Automated Drivingmentioning
confidence: 99%
“…Specifically, various presented information were evaluated to be differently relevant (Ackermann et al, 2019;Merat et al, 2018;Zhang, Vinkhuyzen, & Cefkin, 2018). Information regarding AVs' intention was considered more important than information about whether the vehicle detected the VRU (Mahadevan, Somanath, & Sharlin, 2018). An exploratory study by Merat et al (2018) showed that VRUs rated messages about AVs' starting, stopping and turning maneuvers as significantly more important than information regarding the vehicles' speed.…”
Section: Designing Interactions In Automated Drivingmentioning
confidence: 99%
“…Prior research indicates that pedestrians benefit from information regarding awareness and intent of AVs [26]. This is particularly true in situations where it is difficult to infer a vehicle's intention from other cues (e.g., speed).…”
Section: Investigating the Influence Of External Car Displays On Pedementioning
confidence: 99%
“…Recent work on pedestrian-AV communication also focused on using external displays [7,15,23,26,32,41]. Other channels, such as "eyes" on a car [5], LED stripes [11], projection [4], mobile devices or physical attachments like a waving hand [26] have also been investigated. Whilst generally research has rejected the use of text, a text display was one of the preferred formats reported by Deb et al [9] and Chang et al [4].…”
Section: Automated Car To Pedestrian Communicationmentioning
confidence: 99%
“…Traditional methods of explicit communication in HDVs include indicator lamps, brake lamps, and horns. Current research on AV explicit communication primarily explores the efficacy of additional specialized interfaces such as light-emitting diode message boards, light-emitting diode lights, interactive head lamps, etc., in conveying vehicle intent in the absence of human drivers (Chang et al, 2017(Chang et al, , 2018Habibovic et al, 2018;Mahadevan et al, 2018). Although these approaches are valuable and insightful, there is currently no one standard communication interface.…”
Section: Introductionmentioning
confidence: 99%